The error-related negativity (ERN) is an electrophysiological marker of motor impulsiveness on the Barratt Impulsiveness Scale (BIS-11) during adolescence - Taylor, Jasmine B. (Dev Cogn Neurosci, 2018)
OBJECTIVES: Previous studies have postulated that the error-related negativity (ERN) may reflect individual differences in impulsivity; however, none have used a longitudinal framework or evaluated impulsivity as a multidimensional construct. The current study evaluated whether ERN amplitude, measured in childhood and adolescence, is predictive of impulsiveness during adolescence. METHODS: Seventy-five children participated in this study, initially at ages 7–9 years and again at 12–18 years. The interval between testing sessions ranged from 5 to 9 years. The ERN was extracted in response to behavioural errors produced during a modified visual flanker task at both time points (i.e. childhood and adolescence). Participants also completed the Barratt Impulsiveness Scale − a measure that considers impulsiveness to comprise three core sub-traits − during adolescence. RESULTS: At adolescence, the ERN amplitude was significantly larger than during childhood. Additionally, ERN amplitude during adolescence significantly predicted motor impulsiveness at that time point, after controlling for age, gender, and the number of trials included in the ERN. In contrast, ERN amplitude during childhood did not uniquely predict impulsiveness during adolescence. CONCLUSIONS: These findings provide preliminary evidence that ERN amplitude is an electrophysiological marker of self-reported motor impulsiveness (i.e. acting without thinking) during adolescence.